Pengaruh Pencahayaan Alami Terhadap Kenyamanan Visual Pengguna Ruang Kuliah Gedung Baru Teknik Pengairan UB - Zakaria Priyono Putra (Jurnal Mahasiswa Jurusan Arsitektur, 2018)
Natural lighting is related with the human perception. Lighting is one of the important factor because the visual comfort will affect process of study in class room. Lack of lighting inside the class room will affect productivity and study activities. GBTP is one of the building of Brawijaya University that has 6 floors and used as class room with window ratio ±60% of building surface. However, differentiation of contrast exposure intensity appear in several class room and with a one side lighting because of double loaded-coridor. Aim of this study is to understand human visual comfort towards natural lighting of class room and to understand lighting system engineering to increase class room visual comfort. Dependent variables are exposure level and lighting distribution, while independent variables are window, shading devices, and interior colour. This reserach use experimental method with descriptive- quantitative. Dialux 4.13 is used as the software to know distribution lay out and distributed lighting in the class room. Experimental method also used to analyse the result and to create some recomendation through independent variable engineering that decrease and improve exposure intensity and distribution of light inside the class room.